Studies on Clinico-Etio-Epidemiology of Vomition in Dogs - Khanduri, Rimjhim; Raval, Sunant K.; Sadhu, Dasharath B.; Dave, Keshank M.; Bhanderi, Bharat B.; Kelawala, Divdyesh N. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study of etio-epidemiology of vomition in dogs was carried out amongst the dogs presented at Veterinary Clinical Complex,AAU, Anand. A total of 50 cases of vomiting dogs were selected for this study. Investigation of etiological factors associated with vomitionrevealed that 50.00% vomiting cases were due to dietary abnormalities, 24.00% due to Parvo viral infection, 10.00% due to parasiticinfestation, 8.00% renal disorders, 6.00% due to hepatic disorders, and 2.00% due to pyometra. The epidemiological parameters like sex,breed, and age were recorded. During the sex-wise incidence of vomition was found more in male (64.00 %) than in female (36.00 %)dogs. The breed-wise incidence of vomition was recorded highest (32.00 %)in Mongrel, followed by Labrador Retriever (28.00 %), Spitz(12.00 %), Doberman Pinscher ( 8.00 %), German Shepherd ( 10.00 %), Great Dane 4%, Beagle (2.00 %), Lasa Aphso (2.00 %), and Pug(2.00 %) . The age-wise incidence of vomition was recorded higher (58.00%) in 0-6 months age group, followed by (24%) in 7 months to3 years age group and (18%) in 3-8 years age group. Clinical examination revealed dehydration, dullness, congested to anemic mucusmembranes, inappetence to anorexia, tachycardia, melaena, haematemesis, diarrhea, and clear lungs. On abdominal palpation, therewas mild pain in dogs affected with renal and hepatic disorders
Keywords: Canine parvovirus infection; Epidemiology; Etiology; Incidence; Vomition